PILGRIM COMMUNITY OF DISCIPLES: PILGRIM COMMUNITY OF DISCIPLES: AN ASIAN MODEL OF THE CHURCH - Varayilan, Davis (Asian Horizons, 2012)
The word “church” conveys many different meanings to different people. When Catholics hear the word, they generally think of the hierarchy, the Pope and Roman curia. For many Protestants, “church” means the local community, their congregation. For the followers of other religions, it means a building, an institution. The meaning, belongingness and commitment depend on the image or model the word brings to their mind. The changes of time and context call for new models to explain the mystery of the Church. The Second Vatican Council and the pluralistic context of Asia demand a new model of the Church to convey what it is meant for in Asia. In this article, I propose a model of the Church as Pilgrim Community of Disciples for the pluralistic context of Asia. Pilgrim conveys the eschatological and dynamic nature of the Church, the community points to its historical rootedness in Jesus of Nazareth and the complementary role of institution and charism and disciples suggests the openness needed to learn from co-pilgrims on the way to the fullness of the Kingdom.